Fine Mapping of the “black” Peel Color in Pomegranate (Punica granatum L.) Strongly Suggests That a Mutation in the Anthocyanidin Reductase (ANR) Gene Is Responsible for the Trait - Trainin, Taly; Harel-Beja, Rotem; Bar-Ya’akov, Irit; Ben-Simhon, Zohar; Yahalomi, Rami; Borochov-Neori, Hamutal; Ophir, Ron; Sherman, Amir; Doron-Faigenboim, Adi; Holland, Doron (Frontiers in Plant Science, 2021)
Anthocyanins are important dietary and health-promoting substances present in high quantities in the peel and arils of the pomegranate (Punica granatum L.) fruit. Yet, there is a high variation in the content of anthocyanin among different pomegranate varieties. The ‘Black’ pomegranate variety (P.G.127-28) found in Israel contains exceptionally high levels of anthocyanins in its fruit peel which can reach up to two orders of magnitude higher content as compared to that of other pomegranate varieties’ peel anthocyanins. Biochemical analysis reveals that delphinidin is highly abundant in the peel of ‘Black’ variety. The pattern of anthocyanin accumulation in the fruit peel during fruit development of ‘Black’ variety differs from that of other pomegranates. High anthocyanin levels are maintained during all developmental stages. Moreover, the accumulation of anthocyanin in the fruit peel of ‘Black’ variety is not dependent on light. Genetic analysis of an F2 population segregating for the “black” phenotype reveals that it is determined by a single recessive gene. Genetic mapping of the F2 population using single nucleotide polymorphism (SNP) markers identified few markers tightly linked to the “black” phenotype. Recombination analysis of the F2 population and F3 populations narrowed the “black” trait to an area of 178.5 kb on the draft genome sequence of pomegranate cv. ‘Dabenzi.’ A putative anthocyanidin reductase (ANR) gene is located in this area. Only pomegranate varieties displaying the “black” trait carry a base pair deletion toward the end of the gene, causing a frame shift resulting in a shorter protein. We propose that this mutation in the ANR gene is responsible for the different anthocyanin composition and high anthocyanin levels of the “black” trait in pomegranate.